2020
DOI: 10.1590/0034-761220200268x
|View full text |Cite
|
Sign up to set email alerts
|

Homeless population and COVID-19

Abstract: Resumo O objetivo deste trabalho é propor sugestões práticas para a atuação no atendimento à população em situação de rua diante da pandemia da COVID-19 no Brasil. Com base numa pesquisa qualitativa contendo entrevistas com profissionais da área, análise de informações levantadas num portal de notícias de amplitude nacional e levantamento de artigos, relatórios de pesquisa e documentos informativos de outros países, sugerimos algumas estratégias que podem contribuir para a atuação da gestão municipal, sobretud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
0
11
0
2
Order By: Relevance
“…Their reflections, feelings, and experiences focus on diverse aspects of information, from the lack of information to over-information and misinformation. In this vein, previous studies have raised concerns about the limitations and barriers to access health information in vulnerable groups [ 6 ], an aspect aggravated in the COVID-19 pandemic context in spite of the importance of approaching the situation of this vulnerable group [ 3 , 4 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their reflections, feelings, and experiences focus on diverse aspects of information, from the lack of information to over-information and misinformation. In this vein, previous studies have raised concerns about the limitations and barriers to access health information in vulnerable groups [ 6 ], an aspect aggravated in the COVID-19 pandemic context in spite of the importance of approaching the situation of this vulnerable group [ 3 , 4 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies place the relevance of approaching the situation of homeless people in the pandemic context [ 3 , 4 , 5 , 6 ]. This reality has been analysed in diverse countries and regions worldwide, advancing knowledge about different issues affecting this vulnerable group, some of them contributing to provide solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of literature has found that homeless populations experience high levels of trauma, physical, emotional and mental health struggles, alcoholism, and drug addiction (Deilamizade & Moghanibashi-Mansourieh, 2020;Honorato & Oliveira, 2020;Martin et al, 2020). In addition to these health and housing-related vulnerabilities, PEH are regularly marginalized and stigmatized by society (Karabanow, 2004;Karabanow et al, 2018).…”
Section: Homeless People In the Global Context Of Extreme Eventsmentioning
confidence: 99%
“…From 1997, when this population became a community 'deserving of public policies' (Katz, and reports of cumulative violent acts -often carried out by government in São Paulo itself. Given the increase in the homeless population, with possible expansion due to the crisis generated by the COVID-19 pandemic 1 and the seriousness of this event for people experiencing homelessness, it is possible to start from the premise that this is a topic of empirical and theoretical relevance in the field of policies aimed at social protection (Honorato & Oliveira, 2020).…”
Section: Introductionmentioning
confidence: 99%